STRENGTHENING FAMILIES IN THE DIGITAL ERA: A DIGITAL LIFE BALANCE PROGRAM HELD IN GADUT KANAGARIAN, TILATANG KAMANG SUB-DISTRICT, AGAM DISTRICT - Fikry, Zulian; Sari, Putri Minas; Putra, Yanladila Yeltas; Rizal, Gumi Langerya; Aprisi, Sherly; Termizal, Maharani Tosca; Elvika, Rahma Rezki (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The community service program titled "Strengthening Families in the Digital Era: Digital Life Balance Program in Kanagarian Gadut, Tilatang Kamang District, Agam Regency" aims to enhance parents' understanding of balanced digital technology use within families. The program addresses the impacts of gadget use on the physical, mental, and social health of children and adolescents. The program employed various methods, including psychoeducation, focus group discussions, counseling, and hands-on practice with parents and children. Results indicated a significant increase in participants' understanding of balanced technology use, as evidenced by improved pre-test and post-test scores, along with positive feedback from attendees. Parents particularly valued the practical strategies provided for managing gadget use within the family. By utilizing participatory methods, the program successfully engaged the community and offered new insights into the importance of maintaining a balance between digital and non-digital life in the modern era.